Hubungan Antara Pelayanan Pengurusan Sertifikasi Tanah dan Tingkat Kepuasan Masyarakat - M.Vindy Roulfan Damanik; Muhammad Husni Thamrin Nasution; Walid Mustafa Sembiring (PERSPEKTIF, 2018)
This observation is backgrounded on the condition where the departement of land still found many problems such as unqualified administrative requirements and many other problems have been passed by public in handling the land certificate. This things happened due to unsatisfaction services such as the duration of file handling and also measurements. 6 months is required due to many procedure needed and the long duration of file handling. The theories used in this observation is includes many description in customer relation, the element of service, the service's standard, bureaucracy, and public's satisfaction. The object in this observation is people who taking care on their Land certificate as many as 40 people. The methods in this observation is quantitative method. The result of the research is that according to the analysis and evaluation, found a result that t test is 4,3504 (tcount>ttable) have a positive and significant relation between the service and the satisfaction. the coefficient determination is 33,24%. So we can conclude, that public's satisfaction is affected by the services as many as 33,24% while 66,76% is affected by other factors.Â